On the spectrum of ψ-contracting operators. (2001) - Al-Nayef, Anwar A.
Abstract : The spectrum σ ( A ) of a continuous linear operator A : E → E defined on a Banach space E, which is contracting with respect to the Hausdorff measure of noncompactness, is investigated.